PENERAPAN “ASAS KEADILAN” DALAM SENGKETA KEPAILITAN DALAM RANGKA MELINDUNGI KEPENTINGAN DEBITUR (Studi Putusan : Nomor 44pk/Pdt.Sus-Pailit/2016) - Rachman, Raihan; Muryanto, Yudho Taruno (Fakultas Hukum Universitas Sebelas Maret, 2023)
Bankruptcy is a legal process when a debtor who go through difficulty to pay the debt to the creditor hence it is stated as bankrupt through commercial court. In the court process of bankruptcy legal action, there are principles which become foundation to execute the bankruptcy process in accordance with the Act No. 37 Year 2004 about PKPU (Penundaan Kewajiban Pembayaran Utang/Suspension of debt payment obligations) and Bankruptcy. This research aimed to acknowledge the implementation of justice principle in the bankruptcy legal action between Acrossasia Limited and PT. First Media Tbk, also the power of bankruptcy legal verdict especially on the verdict of No. 44PK/Pdt.Sus-Pailit/2016 which not in accordance with the bankruptcy requirements. This research used normative method which means the writer studied the existing laws and regulations. Moreover, the research used case approach to find a complete picture of a situation. The research results of this article show that this decision has permanent power and execution but in this decision it does not apply as justice which is a condition in bankruptcy.